Human Mesenchymal Stem Cell-Derived Exosomes as Engineering Vehicles of Daunorubicin for Targeted c-Mpl+ AML Therapy - Li C; Wen Y; Wang J; Li L; He Y; Cheng Y; Chen J; Huang J; Ouyang C; Liu Y; Zhou R; Chen H; et al. (International Journal of Nanomedicine)
Chunmou Li,1,* Yuchen Wen,1,* Jiasheng Wang,2 Lindi Li,1 Yue He,2 Yucai Cheng,1 Junru Chen,2 Junbin Huang,1 Cheng Ouyang,1 Yong Liu,1 Ruizhi Zhou,1 Haisheng Chen,2 Fei Li,2 Qiqi Guo,2 Yun Chen,3 Chun Chen,1 Qing Zhang2 1Pediatric Hematology Laboratory, Division of Hematology/Oncology, Department of Pediatrics, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, Guangdong, 518107, People’s Republic of China; 2State Key Laboratory of Biocontrol, School of Life Sciences, Sun Yat-sen University, Guangzhou, Guangdong, 510275, People’s Republic of China; 3Department of Pediatrics, Edmond H. Fischer Translational Medical Research Laboratory, Scientific Research Center, The Seventh Affiliated Hospital, Sun Yat-Sen University, Shenzhen, Guangdong, 518107, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chun Chen, Pediatric Hematology Laboratory, Division of Hematology/Oncology, Department of Pediatrics, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, Guangdong, 518107, People’s Republic of China, Email chenchun@sysush.com Qing Zhang, State Key Laboratory of Biocontrol, School of Life Sciences, Sun Yat-Sen University, Guangzhou, Guangdong, 510275, People’s Republic of China, Email lsszq@mail.sysu.edu.cnBackground: Acute myeloid leukemia (AML) is a highly heterogeneous disease with poor therapeutic outcomes and overall prognosis, particularly in c-Mpl+ AML. c-Mpl, a proto-oncogene, is expressed at significantly higher levels in AML compared to normal human tissue cells. This study aimed to develop a type of targeted exosomes (Exos) capable of delivering anticancer drugs directly to c-Mpl+ AML cells.Methods: Human umbilical cord mesenchymal stem cells (hUCMSCs) were isolated as the source of Exos. Fusion CD63 proteins with varying numbers of thrombopoietin (TPO)-mimic peptides, designed to target c-Mpl, were bioengineered to be expressed on the membranes of hUCMSCs and their derived Exos. The targeting capability of the fusion proteins was assessed using the DUAL membrane system, fluorescence resonance energy transfer efficiency, and endocytosis assays. After encapsulating the anticancer drug daunorubicin (DNR), these targeted Exos were evaluated for their ability to eliminate c-Mpl+ AML cells. Safety and efficacy were further tested in a mouse AML model.Results: Our findings showed that the engineered hUCMSCs-derived Exos demonstrated excellent targeting ability to c-Mpl and a strong propensity for endocytic uptake by c-Mpl+ AML cells. Among the engineered Exos, those with the fusion protein containing three TPO-mimic peptides (CD63-mTPO3), named as m3Exos, exhibited the highest binding affinity for c-Mpl. When loaded with DNR, these engineered Exos (m3Exos@DNR) effectively eliminated c-Mpl+ AML cells in both in vitro and in vivo experiments. Furthermore, safety assessments revealed that therapy-related toxicities were within acceptable limits and associated with manageable side effects.Conclusion: In summary, our results suggest engineered Exos as a highly effective targeted drug delivery vehicle for eliminating c-Mpl+ AML cells while maintaining a favorable safety profile. These findings also provide valuable insights for developing therapeutic strategies for AML and other tumors characterized by specific membrane protein expression.Keywords: c-Mpl, AML, exosome, engineering, targeted therapy